HUBUNGAN ANTARA MANAJEMEN WAKTU DAN DUKUNGAN SOSIAL DENGAN PRESTASI AKADEMIK MAHASISWA YANG BEKERJA - Puspitasari, Widya (EMPATHY Jurnal Fakultas Psikologi, 2013)
Abstract             This research aimed to determine the relationship between Time Management and Social Support with Academic Achievement of Students Working. The subjects of research were 60 students of the Faculty of Industrial Technology IST AKPRIND Yogyakarta. The data collection tools of this research used the Time Management Scale, Social Support Scale and Documentation in the form of a grade point average (GPA) of students who work. Analysis of the statistical method of multiple regression analysis using SPSS 16 for windows. The results of research showed: (1) The Relationship between Time Management and Social Support with Academic Achievement of Students Working with R = 0.558 and F = 12.913 with p = 0.000 (p <0.01), (2) There is a positive relationship between time management to academic achievement with r = 0.487 and p = 0.000 (p <0.01), (3) There is a positive relationship between social support to academic achievement with r = 0.504 and p = 0.000 (p <0.01). Keyword: Time Management, Social Support, Academic Achievement.